Design and Implementation of a Touch-Free Door Lock System Based on Arduino - Susilo, Sidik; Muhamad Nurdin Latif; Erny Listijorini; Shofiatul Ula; Dewi Utami (Politeknik Piksi Ganesha Indonesia, 2025)
This study focuses on designing a touch-free door lock system based on Arduino, utilizing ultrasonic sensors, sound sensors, magnetic switches, and slot locks, following the Pahl and Beitz design methodology. The aim is to develop a reliable system that enhances convenience and reduces the need for physical contact with door locks. The results indicate that the ultrasonic sensor performs effectively in detecting distances, while the magnetic switch operates within a maximum reading range of 10 mm. However, the sound sensor demonstrated low accuracy, requiring multiple claps for successful detection. The findings suggest that the developed product functions as intended, though the limitations of the sound sensor highlight the need for further improvements to optimize precision and responsiveness.